1985
DOI: 10.2134/agronj1985.00021962007700040022x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Utilization of Corn Under Minimal Tillage and Moldboard Plow Tillage. I. Four‐Year Results Using Labeled N Fertilizer on an Atlantic Coastal Plain Soil1

Abstract: Crop responses and N uptake of corn (Zea maysL.) grown with moldboard plow tillage (PT) and minimal tillage (MT) were measured in a 4‐yr field experiment on a Mattapex silt loam soil (finesilty, mixed, mesic, Aquic Hapludult) near Salisbury, MD (Atlantic Coastal Plain region). Labeled ammonium sulfate or ammonium nitrate (15N depleted) was applied annually to the entire area (74 m2) of each plot at five N rates ranging from 0 to 180 or 270 kg N ha−1. Corn dry matter yield, N content, and isotope composition we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
8

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 12 publications
6
41
0
8
Order By: Relevance
“…All primary sources of data, years, range in observed yields, and the predicted optimum N rate for all locations are reported in Table 1. Substantive published research has shown dramatic changes in optimum N rates varying from year to year at the same location (Al- Kaisi and Yin, 2003;Bundy et al, 2011;Eck, 1984;Fenster et al, 1978;Gehl et al, 2005;Ismail et al, 1994;Jokela and Randall, 1989;Mallarino and Ortiz-Torres, 2006;Meisinger et al, 1985;Olson et al, 1986;Peterson and Varvel, 1989;Randall et al, 2003;Rice et al, 1986;Shapiro and Wortmann, 2006;Stecker et al, 1993;Varvel et al, 2007;Vetsch and Randall, 2004;Woodruff et al, 1984). Nonetheless, given the importance of N for both crop production and the environment, no single document addresses the comprehensive nature of the problem or provides realistic and accurate estimates of the present variability in N rate recommendations.…”
Section: ( )mentioning
confidence: 99%
“…All primary sources of data, years, range in observed yields, and the predicted optimum N rate for all locations are reported in Table 1. Substantive published research has shown dramatic changes in optimum N rates varying from year to year at the same location (Al- Kaisi and Yin, 2003;Bundy et al, 2011;Eck, 1984;Fenster et al, 1978;Gehl et al, 2005;Ismail et al, 1994;Jokela and Randall, 1989;Mallarino and Ortiz-Torres, 2006;Meisinger et al, 1985;Olson et al, 1986;Peterson and Varvel, 1989;Randall et al, 2003;Rice et al, 1986;Shapiro and Wortmann, 2006;Stecker et al, 1993;Varvel et al, 2007;Vetsch and Randall, 2004;Woodruff et al, 1984). Nonetheless, given the importance of N for both crop production and the environment, no single document addresses the comprehensive nature of the problem or provides realistic and accurate estimates of the present variability in N rate recommendations.…”
Section: ( )mentioning
confidence: 99%
“…In the process of SOM turnover, the microbial biomass is considered to contribute to the labile pool of nutrients and C. Therefore, increased labile N under NT soils may be related to the general observation of a higher microbial biomass. Experiments with 13 C labelling helped to assess differences in the size of soil active N pool under different tillage practices (Fredrickson et al, 1982;Kitur et al, 1984;Carter and Rennie, 1984;Meisinger et al, 1985;HaugenKozyra et al, 1993). They showed a greater immobilization and a lower ef®ciency of use by the crop of fertilized N under NT.…”
Section: Mineralizable Nitrogen (N) and Microbial Biomassmentioning
confidence: 99%
“…Future research will explore the hypothesis that covalent binding of N into stable forms such as anilide slows the rate of N mineralization while also extending its duration into late season crop growth stages and the subsequent fallow period. As long as the field remains flooded, mineralization of covalently bound N may by ARTICLE IN PRESS Carefoot et al (1990) Wheat-barley/Alberta Clay et al (1990) Corn/Minnesota Kitur et al (1984) Corn/Kentucky Meisinger et al (1985) Corn/Maryland Rice et al (1986) Corn/Kentucky itself be too slow to meet peak crop N demand at the onset of crop reproductive growth in mid-season. Whether the accumulation of phenolic lignin residues and their binding with soil N leads to yield losses can depend on several factors.…”
Section: Agronomic Significance Of Covalently Bound Nmentioning
confidence: 99%